SOCIAL MEDIA ADDICTION AND PSYCHOLOGICAL WELLBEING AMONG COLLEGE AND UNIVERSITY STUDENTS: A QUANTITATIVE ANALYSIS (Contemporary Journal of Social Science Review, 2025)
The objective of this study is to address a gap in the existing literature by exploring the relationship between social media addiction and psychological wellbeing among college and university students, as well as examining the mean differences between students from the two educational levels. The study employed a quantitative, cross-sectional correlational design and used a purposive sampling technique to collect data from 228 students aged 15 to 35 years (M = 20.28, SD = 5.04). Two instruments were used: the Bergen Social Media Addiction Scale (BSMAS) and the Psychological Wellbeing Scale. Data were collected following the APA 7th edition code of conduct and analyzed using IBM SPSS Version 26. The correlational analysis revealed a significant negative relationship between social media addiction and psychological wellbeing, while regression analysis indicated that social media addiction significantly and negatively predicted psychological wellbeing among college and university students. The analysis of mean differences showed that university students scored significantly higher on social media addiction and lower (though not significantly) on psychological wellbeing compared to their college counterparts. The study provides important implications for promoting students’ mental health and managing excessive social media use. These findings suggest the need for awareness programs, digital literacy workshops, and counseling interventions aimed at fostering healthy online behavior. Universities and colleges can also integrate psychological support services to help students balance digital engagement with overall wellbeing.